Konsep Minimalism Dalam Berpakaian: Studi Living Qur’an Surat Al-A’raf ayat 31 Perspektif Produk Pakaian Ansoris.id - Rahmah, Shofa Siti; Subhi, Muhammad Rifa'i (STAI KH. MUHAMMAD ALI SHODIQ TULUNGAGUNG, 2024)
This research is motivated by the rise of unhealthy lifestyles among society today, such as consumerism. On the other hand, the minimalist lifestyle trend emerged as a response to consumer phenomena. In fact, the minimalist lifestyle trend has been taught by Islam through the concept of simple living. In Surah Al-Furqan verse 67, it is explained that Allah commands His servants to be fair in all matters and take the middle path. Regarding clothing, Allah commands us to dress in a way that covers our nakedness. Apart from that, we are allowed to wear nice clothes with the intention of worshiping Allah, so wearing nice clothes in the sense here is not to brag. On the other hand, Allah also emphasizes not to overdress. In line with this, a brand called Ansoris.id applies a minimalist lifestyle concept to its clothing products. The research method used to look at the social situation of Al-Qur'an livelihoods in Ansoris.id clothing products is a qualitative research method. The sample is the clothing brand manufacturer Ansoris.id. Data collection techniques use interviews. Through interviews we can see how the minimalist concept is applied to Ansoris.id clothing products. Keywords:Minimalism Lifestyle, Living Qur'an, Muslim Clothing.